2016
DOI: 10.1155/2016/1690474
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Beraprost Sodium on Diabetic Nephropathy by Inhibiting Inflammation and p38 MAPK Signaling Pathway in High-Fat Diet/Streptozotocin-Induced Diabetic Rats

Abstract: Background. p38 mitogen-activated protein kinase (MAPK) plays a crucial role in regulating signaling pathways implicated in inflammatory processes leading to diabetic nephropathy (DN). This study aimed to examine p38 MAPK activation in DN and determine whether beraprost sodium (BPS) ameliorates DN by inhibiting inflammation and p38 MAPK signaling pathway in diabetic rats. Methods. Forty male Sprague Dawley (SD) rats were randomly divided into the normal control group, type 2 diabetic group, and BPS treatment g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 49 publications
2
29
0
Order By: Relevance
“…Previous study reported that BPS ameliorated proteinuria and renal histologic lesions in diabetic rats. 24 Experimental study documented that BPS had a beneficial effect on DN. 25 Recent study demonstrated that BPS attenuated characteristics of metabolic syndrome in obese rats.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study reported that BPS ameliorated proteinuria and renal histologic lesions in diabetic rats. 24 Experimental study documented that BPS had a beneficial effect on DN. 25 Recent study demonstrated that BPS attenuated characteristics of metabolic syndrome in obese rats.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Peng et al. reported that intraperitoneal administration of PGI 2 in type 2 diabetes rats inhibited the p38 mitogen‐activated protein kinases signaling pathway in kidney tissue, reduced inflammatory cytokines and suppressed excretion of albumin. Thus, numerous studies reported on various cytokines that show renoprotective action.…”
Section: Discussionmentioning
confidence: 99%
“…SAA inhibits activation of the NF-κB and p38 MAPK signaling pathways in 5/6Nx rats Several studies have suggested that the NF-κB and p38 MAPK signaling pathways are closely associated with kidney inflammation [13,[20][21][22][23]. Thus, levels of major proteins of the NF-κB and p38 MAPK signaling pathways were measured during CKD.…”
Section: Biochemical Parameters In Experimental Animalsmentioning
confidence: 99%
“…It has been reported that the activation of p38 mitogenactivated protein kinase (MAPK), a member of the family of MAPKs, plays a key role in kidney inflammation [22,23]. The activation of p38 MAPK can promote the production of proinflammatory cytokines and regulate cellular apoptosis during renal injury.…”
Section: Introductionmentioning
confidence: 99%